Word Frequency and Lexical Diffusion - Phillips, B. author. aut Link
XIV, 252 p.
Keywords: This study of word frequency effects on sound change provides a resolution of the Neogrammarian controversy. Betty S. Phillips discusses the implications for phonology and historical linguistics of certain types of change affecting the most frequent words first and other types of change affecting the least frequent words first.